2022
DOI: 10.1021/acsabm.2c00358
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Silicone Oil with Tunable Payload for Antibacterial Applications

Abstract: Bacterial infections are a hurdle to the application of medical devices, and in the United States alone, more than one million infection cases are reported annually from indwelling medical devices. Infections not only affect the function of medical devices but also risk the lives and health of patients. Nitric oxide (NO) has been used as an antibacterial therapy that kills bacteria without causing resistance and provides many therapeutic effects such as anti-inflammation, antithrombosis, and angiogenesis. Sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…99 The IL surface of silicone oil has been used to release nitric oxide, which itself has antimicrobial and antithrombotic properties. 100 Endothelial cells tend to grow and migrate on PDMS IL surfaces, which is important for the endothelialization of implanted devices that come into contact with blood. 101 Lee et al reported a lubricated immunocapsid probe surface (LIPS) to improve performance and resist FBR.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…99 The IL surface of silicone oil has been used to release nitric oxide, which itself has antimicrobial and antithrombotic properties. 100 Endothelial cells tend to grow and migrate on PDMS IL surfaces, which is important for the endothelialization of implanted devices that come into contact with blood. 101 Lee et al reported a lubricated immunocapsid probe surface (LIPS) to improve performance and resist FBR.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…50 Their goal was to create an easily manufactured material that would not only release NO but also prevent one of the most significant problems facing NO-doped materials: that fouling of the surface with proteins and other biological materials would mask the interface, slowing and eventually preventing NO release. 51,52 Using a multicomponent liquid-infused system to address this was successful. NO generated by both the leaching and degradation of the SNAP within the silicone solid slowly infused into the silicone liquid, releasing NO at consistent rates (0.35-0.42 × 10 −10 mol cm −2 min −2 ) over seven days and significantly reducing platelet adhesion compared to surfaces with a liquid coating alone.…”
Section: Secondary Component: Nitric Oxidementioning
confidence: 99%
“…A similar methodology was reported with other SR-based medical devices for the use of urinary catheters and insulin cannula with long-term NO release and reduced SNAP leaching and protein fouling in addition to excellent antibacterial, antifouling, and biocompatible properties. ,, This is a simple and promising approach to generate a LINORel surfaces on prefabricated medical devices and therefore holds huge potential in clinical translation. Recently, a novel method to generate NO-releasing Si oil with proactive antibacterial properties was reported that involved covalent immobilization of the NO donor to Si oil or generation of NO-releasing Si oil by nitrosation of thiolated Si oils. , Such oils can be infused on the PDMS surfaces that are often used for biomedical device applications to create antibacterial interfaces. NO release from these surfaces can be controlled by modulating the NO payload on the basis of the type of application.…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 99%
“…Recently, a novel method to generate NO-releasing Si oil with proactive antibacterial properties was reported that involved covalent immobilization of the NO donor to Si oil or generation of NO-releasing Si oil by nitrosation of thiolated Si oils. 208,209 Such oils can be infused on the PDMS surfaces that are often used for biomedical device applications to create antibacterial interfaces. NO release from these surfaces can be controlled by modulating the NO payload on the basis of the type of application.…”
Section: No-releasing Combinational Surfaces With Antimicrobial and A...mentioning
confidence: 99%